Temperature Dependence of Structure and Ionic Conductivity of LiTa2PO8Ceramics - Dai, Ruoyu; Avdeev, Maxim; Kim, Seung Joo; Prasada Rao, Rayavarapu; Adams, Stefan (Chemistry of Materials, 2022)
LiTa2PO8 has recently been reported as a new fast Li-ion conducting structure type within the series of Lix(MO6/2)m(TO4/2)n polyanion oxides. Here, we demonstrate the preparation of LiTa2PO8 by solid-state syntheses, clarify the temperature dependence of lithium distribution and ionic conductivity, and study the structural stability, densification, and achievable total conductivity as a function of sintering conditions synergizing experimental neutron and X-ray powder diffraction and electrochemical studies with computational energy landscape analyses and molecular dynamics simulations. A total room temperature conductivity of 0.7 mS cm-1 with an activation energy of 0.27 eV is achieved after sintering at 1323 K for 10 h. Spark plasma sintering yields high densification >98%, highly reproducible bulk conductivities of 2.8 mS cm-1, in agreement with our bond valence site energy-based pathway predictions, and total conductivities of 0.6 mS cm-1 within minutes. Powder diffraction studies from 3 to 1273 K reveal a reversible flipping of the monoclinic angle from above to below 90° close to room temperature as a consequence of rearrangements of the mobile ions that change the detailed pathway topology. A consistent model of the temperature-dependent Li redistribution, conductivity anisotropy, and transport mechanism is derived from a synopsis of diffraction experiments, experimental conductivity studies, and simulations. Due to the limited electrochemical window of Lix(TaO6/2)2(PO4/2)1 (LTPO), a direct contact with Li metal or high voltage cathode materials leads to degradation, but as demonstrated in this work, semi-solid-state batteries, where LTPO is protected from direct contact with lithium by organic buffer layers, achieve stable cycling.
Keywords: Conducting structure; Densifications; Diffraction studies; Direct contact; Ion-conducting; Polyanions; Solid-state synthesis; Structural stabilities; Structure type; Temperature dependence